A Comparative Study Of Pre-Operative Cone Beam Computed Tomography Findings Versus Intraoperative Surgical Findings Of Facial Canal Overhang In Otosclerosis - .G, Agaman; M. K, Rajasekar.; Ajitha.K, Ajitha.K (Journal of Neonatal Surgery, 2025)
Introduction: Otosclerosis is a common cause of adult conductive hearing loss, characterized by abnormal bone remodeling of the otic capsule, predominantly affecting the stapes footplate. Facial canal overhang is a critical anatomical variation that can complicate stapedotomy surgery, increasing the risk of facial nerve injury. Cone Beam Computed Tomography (CBCT) has emerged as a promising imaging modality for detailed preoperative evaluation of temporal bone anatomy. This study compares preoperative CBCT findings with intraoperative surgical findings in identifying facial nerve overhang in otosclerosis patients. Materials & Methods: A prospective comparative study was conducted at Bharath Medical College Hospital & Research Institute, Chennai, involving 50 patients diagnosed with otosclerosis who underwent stapedotomy. All patients underwent preoperative CBCT imaging, followed by intraoperative assessment for facial nerve overhang. Data were analyzed using descriptive statistics, Chi-square tests, and Kappa statistics to determine agreement between CBCT and surgical findings. Results: Facial nerve overhang was identified preoperatively in 6 patients (12%) on CBCT and was confirmed intraoperatively in all these cases, showing 100% agreement. The diagnostic performance of CBCT showed a sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of 100% each. This highlights CBCT's high reliability for preoperative assessment. Conclusion: CBCT is an accurate and dependable imaging tool for detecting facial nerve overhang in otosclerosis surgery. Its use can aid surgeons in identifying anatomical variations, improving surgical planning, and reducing intraoperative complications.